Pengaruh Film Alternatif terhadap Emosi - Ananda Sevma Ardyaksa; Thomas Dicky Hastjarjo (Faculty of Psychology, Universitas Gadjah Mada, 2016)
The purpose of this experiment was to understand the impacts of alternative movies on emotion. Posttest only design using proxy pretest was used. Twenty four undergraduate students of Universitas Gadjah Mada were divided into three groups based on their movies preferences: alternative group, mainstream group, and control group. Emotion as the dependent variable was measured post treatment using DES (Differential Emotion Scale) and was analyzed with one-way ANOVA. The results showed that there was no differences in emotion between the three groups (F=.376 (p>.05).